2022
DOI: 10.21037/jtd-22-790
|View full text |Cite
|
Sign up to set email alerts
|

Middle to long-term outcomes of surgical repair for atrioventricular septal defect: a single-center study

Abstract: Background: The exact incidence and predictors of mortality and left atrioventricular valve (LAVV) reoperation in congenital atrioventricular septal defect (AVSD) repair are still unclear. This study analyzed the middle to long-term outcomes of surgical repair for AVSD.Methods: A total of 150 patients (69 males and 81 females) who underwent AVSD repair at Children's Hospital of Fudan University from January 2013 to December 2021 were divided into complete defect group (C-group, 67 cases), transitional defect g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
1
1
Order By: Relevance
“…Our results were supported by the study of [24] as they reported that The early mortality rate was 2.5% (1/40). The survival rate was 90% (95% CI: 76-96) at 10 years and 83% (95% CI: 60-94) at 20 years.…”
Section: Regarding Thecomparison Of Preoperative Resultssupporting
confidence: 89%
“…Our results were supported by the study of [24] as they reported that The early mortality rate was 2.5% (1/40). The survival rate was 90% (95% CI: 76-96) at 10 years and 83% (95% CI: 60-94) at 20 years.…”
Section: Regarding Thecomparison Of Preoperative Resultssupporting
confidence: 89%
“…The LAVVR recurrent rate is lower than the rate reported by Fortuna and his colleagues ( 29 ). The estimated overall mortality and re-operation rate were 2.5% and 6.4% in our study, which were similar to previous studies ( 30 - 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, a deeper analysis reveals that there was a very high rate of preoperative moderate or greater LAVV regurgitation and pulmonary hypertension, which were two of the major factors associated with mortality. Moderate or greater LAVV regurgitation was present in 76.1% of patients with complete AVSD in this study (10), compared to 20% of our patients in Melbourne (2) and 30% in Texas (4). Both LAVV regurgitation and pulmonary hypertension were particularly common in patients under 3 months of age, who were also at increased risk of mortality.…”
contrasting
confidence: 58%
“…Cai et al (10) report their experience with 150 patients across the spectrum of AVSD who underwent complete repair at Fudan University between 2013 and 2021. They observed an early mortality of 10% in the complete AVSD group, 1.8% in the partial AVSD group and 0% in the transitional AVSD group.…”
mentioning
confidence: 99%